Coral diseases and bleaching on Colombian Caribbean coral reefs - Navas-Camacho, Raúl (2010)
Since 1998 the National Monitoring System for the Coral Reefs of Colombia (SIMAC) has monitored the occurrence of coral bleaching and diseases in some Colombian coral reefs (permanent stations at San Andres Island, Rosario Islands, Tayrona, San Bernardo Islands and Urabá). The main purpose is to evaluate their health status and to understand the factors that have been contributing to their decline. To estimate these occurrences, annual surveys in 126 permanent belt transects (10x2m) with different depth intervals (3-6 meters, 9-12 meters and 15-18 meters) are performed at all reef sites. Data from the 1998-2004 period, revealed that San Andrés Island had many colonies with diseases (38.9 colonies/m2), and Urabá had high numbers with bleaching (54.4 colonies/m2). Of the seven reported coral diseases studied, Dark Spots Disease (DSD), and White Plague Disease (WPD) were noteworthy because they occurred in all Caribbean monitored sites, and because of their high interannual infection incidence. Thirty five species of scleractinian corals were affected by at least one disease and a high incidence of coral diseases on the main reef builders is documented. Bleaching was present in 34 species. During the whole monitoring period, Agaricia agaricites and Siderastrea siderea were the species most severely affected by DSD and bleaching, respectively. Diseases on species such as Agaricia fragilis, A.grahamae, A. humilis, Diploria clivosa, Eusmilia fastigiata, Millepora complanata, and Mycetophyllia aliciae are recorded for first time in Colombia. We present bleaching and disease incidences, kinds of diseases, coral species affected, reef localities studied, depth intervals of surveys, and temporal (years) variation for each geographic area. This variation makes difficult to clearly determine defined patterns or general trends for monitored reefs. This is the first long-term study of coral diseases and bleaching in the Southwestern Caribbean, and one of the few long term monitoring studies on coral diseases worldwide